Нелегкий флирт с удачей - Разумовский Феликс (Крылов, 2004)
Экземпляры: Ф. 13 (20200203) / Инвентарный номер: 47579 / Цена: 50.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Р 17 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44